The Endothelial Mechanotransduction Protein Platelet Endothelial Cell Adhesion Molecule-1 Is Influenced by Aging and Exercise Training in Human Skeletal Muscle - Gliemann, Lasse; Rytter, Nicolai; Piil, Peter; Nilton, Jannik; Lind, Thomas; Nyberg, Michael; Cocks, Matthew; Hellsten, Ylva (Frontiers in physiology, 2018)
The aim was to determine the role of aging and exercise training on endothelial mechanosensor proteins and the hyperemic response to shear stress by passive leg movement. We examined the expression of mechanosensor proteins and vascular function in young ( = 14, 25 ± 3 years) and old ( = 14, 72 ± 5 years) healthy male subjects with eight weeks of aerobic exercise training. Before and after training, the hyperaemic response to passive leg movement was determined and a thigh muscle biopsy was obtained before and after passive leg movement to assess the acute effect of increased shear stress. Biopsies were analyzed for protein amount and phosphorylation of mechanosensor proteins; Platelet endothelial cell adhesion molecule-1 (PECAM-1), Vascular endothelial cadherin, Vascular endothelial growth factor receptor-2 and endothelial nitric oxide synthase (eNOS). Before training, the old group presented a lower hyperaemic response to passive leg movement and a 35% lower ( < 0.05) relative basal phosphorylation level of PECAM-1 whereas there was no difference for the other mechanosensor proteins. After training, the eNOS protein amount, the amount of PECAM-1 protein and the passive leg movement-induced phosphorylation of PECAM-1 were higher in both groups. The hyperaemic response to passive leg movement was higher after training in the young group only. Aged individuals have a lower hyperaemic response to passive leg movement and a lower relative basal phosphorylation of PECAM-1 than young. The higher PECAM-1 phosphorylation despite a similar hyperemic level in the aged observed after training, suggests that training improved shear stress responsiveness of this mechanotransduction protein.